2016
DOI: 10.5114/wo.2015.51825
|View full text |Cite
|
Sign up to set email alerts
|

Methods and results of locoregional treatment of brain metastases in patients with non-small cell lung cancer

Abstract: This article presents methods and results of surgery and radiotherapy of brain metastases from non-small cell lung cancer (BMF-NSCLC). Patients with single BMF-NSCLC, with Karnofsky score ≥ 70 and controlled extracranial disease are the best candidates for surgery. Stereotactic radiosurgery (SRS) is recommended in patients with 1–3 BMF-NSCLC below 3–3.5 cm, with minor neurological symptoms, located in parts of the brain not accessible to surgery, with controlled extracranial disease. Whole brain radiotherapy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…In some cancer centers, there are no criteria for administering SRS and WBRT is used an alternative strategy for patients with limited BM. However, WBRT alone only extends the median survival time by up to 6 months (9,10). WBRT plus in-field radiotherapy boost is an effective strategy for improving the intracranial control rate (ICR) and selecting patients who could experience significant survival benefits (11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…In some cancer centers, there are no criteria for administering SRS and WBRT is used an alternative strategy for patients with limited BM. However, WBRT alone only extends the median survival time by up to 6 months (9,10). WBRT plus in-field radiotherapy boost is an effective strategy for improving the intracranial control rate (ICR) and selecting patients who could experience significant survival benefits (11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Radiotherapy, as an important treatment for controlling neurologic symptoms and prolonging survival, is widely used in patients with BMs. During the past 50 years, whole-brain radiotherapy (WBRT) has been the standard treatment for BMs, but WBRT alone has an unsatisfactory effect with an intracranial control rate (ICR) of 60% and a median survival of just 3–6 months 7,8. Several studies have shown that WBRT plus an in-field radiotherapy boost (RTB) for BMs could improve ICR versus WBRT alone, and select patients could experience significant survival benefits 9–12…”
Section: Introductionmentioning
confidence: 99%